Soybean‐Oil Lipid Minimization for Prevention of Intestinal Failure–Associated Liver Disease in Late‐Preterm and Term Infants With Gastrointestinal Surgical Disorders. Issue 6 (19th September 2020) - Gupta, Kunal; Wang, Hongyue; Amin, Sanjiv B.
Abstract: Background: Intestinal failure‐associated liver disease (IFALD), a multifactorial disease, is common among infants with gastrointestinal surgical disorders (GISDs). Prolonged soy‐based intravenous lipid emulsion (S‐ILE) intake is associated with IFALD, but preventive studies of limiting S‐ILE have been inconclusive. Furthermore, a double–blind, randomized preventive trial (DBRPT) of S‐ILE intake has not been performed in infants with GISDs. Our objective was to compare the effect of 1 g/kg/d vs 2 g/kg/d S‐ILE intake for 6 weeks on the incidence of IFALD and the rate of rise of direct bilirubin (DB) in infants with GISDs. Methods: A DBRPT was conducted in infants with GISDs at ≥34 weeks' gestational age (GA) admitted to the NICU within 72 hours after birth. Infants were randomized in a 1:1 ratio to receive either 1 or 2 g/kg/d S‐ILE for 6 weeks. IFALD was defined as DB ≥2 mg/dL. Results: Forty infants were studied. The 2 groups had similar clinical characteristics except for GA and blood group incompatibility. Thirty percent of infants in each group developed IFALD ( P = .94). However, infants in the group receiving 1 g/kg/d S‐ILE (n = 20) had a lower rate of rise of DB compared with infants in the group receiving 2 g/kg/d S‐ILE (n = 20). Conclusions: Reducing S‐ILE intake for 6 weeks in infants with GISD at ≥34 weeks' GA may not prevent IFALD. The extrapolated data on the rate of rise of DB suggest a possible risk of earlier development of IFALD with S‐ILE intake of 2 g/kg/d, as compared with 1 g/kg/d, beyond the 6‐week study period.